Juridical Analysis of Providing Compensation Money for Certain Hours of Work by Outsourcing Companies Based on the Job Creation Constitution - Yana Indawati (Yayasan Multidimensi Kreatif, 2023)
The enactment of the Job Creation Law and its derivative regulations PP No. 35 of 2021, one of which is about contract workers reaping the pros and cons. The Job Creation Law changes, deletes and inserts new Articles in the Manpower Law. Purpose: This provision is something new, so the purpose of this research is to analyze normatively juridically regarding the rules starting from PKWT, Compensation Policy and Compensation according to experts in outsourcing companies. Method: The type of research used in the preparation of this paper is juridical analysis. Result: There is unclear source of funding for compensation and the provision of compensation is considered discriminatory. The source of compensation funding should have become a contribution that must be paid by employers and employers/users and is bound by the provisions of the law. Conclusion: Workers/laborers should be equally entitled to compensation money without any form of discrimination, this is in accordance with what is mandated by the 1945 Law, Article 28I paragraph (2) and Article 38 paragraph (3) of Law Number 39 of 1999 concerning Rights Human Rights